Rupatadine for the treatment of allergic rhinitis and urticaria. (January 2011) - Metz, Martin; Maurer, Marcus
Allergies are a widespread group of diseases of civilization and most patients are still undertreated. Since histamine is considered to be the most important mediator in allergies such as allergic rhinitis and urticaria, the most commonly used drugs to treat these disorders are antihistamines acting on the histamine 1 (H1) receptor. The currently available antihistamines, however, have significant differences in their effects and safety profiles. Furthermore, the Allergic Rhinitis and its Impact on Asthma initiative calls for additional desirable properties of antihistamines. Here, we review the profile of rupatadine, a new dual platelet-activating factor and H1-receptor antagonist that fulfils these criteria and therefore offers an excellent option for the treatment of allergic diseases.